2015
DOI: 10.1093/mnras/stv1234
|View full text |Cite
|
Sign up to set email alerts
|

The origin of spin in galaxies: clues from simulations of atomic cooling haloes

Abstract: In order to elucidate the origin of spin in both dark matter and baryons in galaxies, we have performed hydrodynamical simulations from cosmological initial conditions. We study atomic cooling haloes in the redshift range 100 > z > 9 with masses of order 10 9 M at redshift z = 10. We assume that the gas has primordial composition and that H 2 -cooling and prior star-formation in the haloes have been suppressed. We present a comprehensive analysis of the gas and dark matter properties of four halos with very lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 45 publications
6
36
1
1
Order By: Relevance
“…Conversely the tidal field strength is low t1 = 0.2 in regions with thin converging filaments which bring in cold material fast and lead to the formation of the most massive black hole in a spheroidal dominated host. Tidal torque theory has been shown by Gonzalez et al (2016) to explain the initial spin of galaxies in hydrodynamic simulations at high redshifts, and Prieto et al (2015) have found that halos with fewer filaments tend to have larger spin. This is in agreement with the examples we have presented here, where the disc galaxies tend to lie in regions with two main filaments, and the low angular momentum galaxies that host black holes lie at the centers of a more symmetric arrangement of multiple filaments.…”
Section: The Origin Of the Fastest Black Hole Growth: Tidal Field Strmentioning
confidence: 93%
“…Conversely the tidal field strength is low t1 = 0.2 in regions with thin converging filaments which bring in cold material fast and lead to the formation of the most massive black hole in a spheroidal dominated host. Tidal torque theory has been shown by Gonzalez et al (2016) to explain the initial spin of galaxies in hydrodynamic simulations at high redshifts, and Prieto et al (2015) have found that halos with fewer filaments tend to have larger spin. This is in agreement with the examples we have presented here, where the disc galaxies tend to lie in regions with two main filaments, and the low angular momentum galaxies that host black holes lie at the centers of a more symmetric arrangement of multiple filaments.…”
Section: The Origin Of the Fastest Black Hole Growth: Tidal Field Strmentioning
confidence: 93%
“…Pichon et al 2011;Prieto et al 2015;Danovich et al 2015) is a robust motivation to study the MT process at different scales in the first galaxies. In the following, we analyze the MT process on kpc ( 0.1R vir ) scales.…”
Section: Mass Transport In the Discmentioning
confidence: 99%
“…In this picture Pichon et al 2011;Stewart et al 2011bStewart et al , 2013Codis et al 2012Codis et al , 2015Danovich et al 2012Danovich et al , 2015Prieto et al 2015;Tillson et al 2015), the particularly high angular momentum of cold flow gas is related to its coherent, filamentary origin, coupled with the specific geometry of the cosmic web in the environment of a given galaxy. These filamentary cold flows deliver significant angular momentum to galaxy halos, with the cold gas orbiting for ∼1−2 dynamical times before spiraling into the central galaxy.…”
Section: Introductionmentioning
confidence: 99%